Is there time for Software Testing in the Indie Games Development?: A survey with practitioners of the game industry - de Oliveira Neto, José Nunes; Viana, Davi; Sá, Eveline; Rivero, Luis; Lopes, Rafael Fernandes; Silva, Francisco (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
In 2018, the game industry made about 137,9 billion dollars worldwide in a very competitive market, since each day new games are launched. Games can be created by large development companies; or by small teams with few resources, which pursue innovation and originality in games, commonly referred to as indie games. Regardless of the size of the organization and/or team, the complexity of the development related to the production of such software is similar. In order to deliver high quality games, the practitioners carry out software tests during the production of their indie games. These tests aim to analyze the specific characteristics of this type of software, such as the degree of entertainment and playability aspects. However, there still no consensus about how the test activities are performed during the development process of indie games. This paper presents a survey to identify the test practices during the development of indie games, aiming to understand how these activities are performed. As a result, we identified that developers worry about the execution of tests during the development of indie games, focusing on techniques that consider more than one inherent aspects of the game. Within the aspects that these developers focus on, we can name: the identification of bugs, verification of playability aspects and degree of entertainment of the game.